Modelling the propagation of a radar signal through concrete as a low-pass filter - Shaari, A.; Millard, S. G.; Bungey, J. H. (Elsevier Ltd, 2004)
The knowledge of how a dispersive, dielectric medium such as concrete affects a propagating short electromagnetic pulse used in ground penetrating radar (GPR) is helpful both in the interpretation of radar results and in the prediction/modelling of expected radar measurements. Although there are a number of published results on the frequency-dependent, dielectric properties of media such as concrete and soils, the use of this information is still relatively small, primarily due the lack of a reliable method of applying these properties to propagating radar pulses. Modelling the dielectric medium as low-pass filter is one solution to this difficulty. In this paper the propagation of short pulses in concrete with known frequency-dependent properties is studied. The extent of how the pulses are attenuated and distorted is analysed and the implications on GPR applications are also discussed